Chain dynamics of human dermis by Thermostimulated currents: A tool for new markers of aging. Issue 1 (24th May 2018) - Samouillan, V.; Tang, R.; Dandurand, J.; Lacabanne, C.; Lacoste‐Ferré, M.‐H.; Villaret, A.; Nadal‐Wollbold, F.; Schmitt, A.‐M.
Abstract: Background/purpose: The purpose of this clinical study was to identify dielectric markers to complete a previous thermal and vibrational study on the molecular and organizational changes in human dermis during intrinsic and extrinsic aging. Methods: Sun‐exposed and non‐exposed skin biopsies were collected from 28 women devised in two groups (20‐30 and ≥60 years old). The dielectric relaxation modes associated with localized and delocalized dynamics in the fresh and dehydrated state were determined by the Thermostimulated currents technique (TSC). Results: Intrinsic and extrinsic aging induced significant evolution of some of the dielectric parameters of localized and delocalized dynamics of human skin. With photo‐aging, freezable water forms a segregated phase in dermis and its dynamics is close to free water, what evidences the major role of extrinsic aging on water organization in human skin. Moreover, TSC indicators highlight the restriction of localized mobility with intrinsic aging due to glycation, and the cumulative effect of chronological aging and photo‐exposition on the molecular mobility of the main structural proteins of the dermis at the mesoscopic scale. Conclusion: TSC is a well‐suited technique to scan the molecular mobility of human skin. It can be uses as a relevant complement of vibrational and thermal characterization to follow human skin modifications with intrinsic and extrinsic aging.